The impact of sand and clay substratum types on the properties of tropical peat soils and oil palm (Elaeis guineensis) production - Naspendra, Zuldadan; Hijri, Nurul; Awalina, Rahmi; Harianti, Mimien; Hermansah, Hermansah (Brawijaya University, 2025)
Research on peatlands has become increasingly interesting in recent years, particularly in tropical regions. In these regions, including Indonesia, peatlands develop over sand and clay substrata and are widely utilized for oil palm cultivation. However, the influence of substratum type on palm yield remains poorly understood. This study aimed to a) investigate the morphological and physical characteristics of peat soils formed over sand and clay substrata and b) examine the relationship between peat soil substratum types (sand and clay) and oil palm production. Soil samples were collected from three blocks of an oil palm plantation in Pesisir Selatan, West Sumatra, and then were analyzed in a soil laboratory. Additionally, fresh fruit bunch (FFB) yield data from the past six years for each block were also collected from the plantation records. The results indicated that peat soil formed over clay substratum (L) was more mature (sapric), with lower fiber content, higher ash content, lower organic matter content, higher moisture content, and higher pH compared to peat soils formed over sand substratum (P1 and P2). The average annual fresh fruit bunch production from palms cultivated on peat soil with a clay substratum (19.68-20.85 t/ha/yr) was 11-16% higher than that of palms on peat soil with sand substratum (23.52 t/ha/yr). Among the peat soil properties analyzed, water content, ash content, and soil pH had the most significant positive effects on oil palm production. These findings highlight the critical role of substratum type in influencing oil palm yield.